Case Control Study on Radioactive Stents Versus Conventional Stents for Inoperable Esophageal Squamous Cell Carcinoma. Issue 4 (August 2020) - Li, Li-Feng; Lv, Lu-Lu; Xu, Yuan-Shun; Cao, Chi; Fu, Yu-Fei
Abstract : Purpose: The purpose of this study was to compare the relative clinical efficacy of radioactive and normal stent insertion for the treatment of inoperable obstructive esophageal squamous cell carcinoma (OESCC). Materials and Methods: Between January 2014 and December 2018, consecutive OESCC patients were treated via either radioactive or normal stent insertion. Results: A total of 42 and 39 OESCC patients were treated via radioactive and normal stent insertion, respectively. These procedures were both technically and clinically successful in all patients. Massive hemorrhage was observed in 7 (16.7%) and 1 (2.6%) patients in radioactive and normal stent groups, respectively ( P =0.080). Median stent patency durations were 175 and 136 days in radioactive and normal stent groups, respectively ( P =0.004). Median overall survival were 187 and 145 days in the radioactive and normal stent groups, respectively ( P =0.011). Conclusion: Relative to normal stent, radioactive stents showed a higher patency and overall survival in OESCC patients.